a^3+2a^2-a-2. ans: (a+2) (a+1)(a-1)
Answers
Answered by
4
a^3 + 2a^2 - a - 2
= a^2 ( a +2) - 1 (a+2)
= (a+2) (a^2 - 1)
= (a +2) [ a^2 - 1^2]
= (a+2)(a+1)(a-1)
= a^2 ( a +2) - 1 (a+2)
= (a+2) (a^2 - 1)
= (a +2) [ a^2 - 1^2]
= (a+2)(a+1)(a-1)
Answered by
3
a³ +2a² -a-2
a²(a+2) -1(a+2)
(a²-1) (a+2)
(a²-1²) (a+2)
(a+1)(a-1)(a+2)
I hope this will help you
-by ABHAY
a²(a+2) -1(a+2)
(a²-1) (a+2)
(a²-1²) (a+2)
(a+1)(a-1)(a+2)
I hope this will help you
-by ABHAY
Similar questions
Computer Science,
9 months ago
India Languages,
1 year ago
Science,
1 year ago
Biology,
1 year ago
Math,
1 year ago